2016
DOI: 10.1080/10810730.2016.1222036
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Patient Characteristics and the Amount of Arthritis Medication Information Patients Receive

Abstract: Little is known about factors associated with receipt of medication information among arthritis patients. This study explores information source receipt and associations between demographic and clinical/patient characteristics and the amount of arthritis medication information patients receive. Adult patients with osteoarthritis (OA) or rheumatoid (RA) arthritis (n = 328) completed an online cross-sectional survey. Patients reported demographic and clinical/patient characteristics and the amount of arthritis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…To our surprise, the factor, medicine-related questions, is the most key point to affect medication adherence, which suggested that explaining medicine-related questions especially error in directions and information concerning medicines clearly to patients when starting treatment may enhance medication adherence in IRD patients. 25 , 32 , 33 Besides, we found that the two questions of missing dose and adjust dosage or stop taking the medicine without doctor’s directions were prominent. Consequently, interventions such as medication reminders and regular follow-up target adherence must be tailored to the particular illness-related demands experienced by the patients.…”
Section: Discussionmentioning
confidence: 91%
“…To our surprise, the factor, medicine-related questions, is the most key point to affect medication adherence, which suggested that explaining medicine-related questions especially error in directions and information concerning medicines clearly to patients when starting treatment may enhance medication adherence in IRD patients. 25 , 32 , 33 Besides, we found that the two questions of missing dose and adjust dosage or stop taking the medicine without doctor’s directions were prominent. Consequently, interventions such as medication reminders and regular follow-up target adherence must be tailored to the particular illness-related demands experienced by the patients.…”
Section: Discussionmentioning
confidence: 91%
“…A study by Geryk et al confirmed that greater receipt of information was associated with greater medication adherence, use of more medications and with more satisfaction with doctor medication-related support, but conversely also with greater medication-taking concerns [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in the quantitative data collection that showed that patients considered almost all information items as important but were not informed thereof. It appears that patients consistently have unmet information needs, which can have direct implications for optimal pharmacotherapy [ 1 4 ]. In this study, patients indicated that medication information should be tailored to their individual needs.…”
Section: Discussionmentioning
confidence: 99%
“…Providing appropriate medication information to patients is of utmost importance for optimal pharmacotherapy, medication adherence and disease control [1,2]. Patients with inadequate knowledge about their medication, receiving inappropriate or non-understandable information are less likely to adhere to their therapy, which could lead to inadequate medication use and decreased therapy efficacy [3,4].…”
Section: Introductionmentioning
confidence: 99%